Bloody sixteen the USS Oriskany and Air Wing 16 during the Vietnam War - Fey, Peter, (Naval commander) (Potomac Books, 2018)
Strategy and reality collide in Peter Fey's gripping history of aircraft carrier USS Oriskany's three deployments to Vietnam with Carrier Air Wing 16 (CVW-16). Fey portrays the Oriskany and its heroes in an indelible memorial to the fallen of CVW-16 in hopes that the lessons learned from such strategic disasters are not forgotten in today's sphere of war-bent politics.